Analysis of the Influence of Institutional Ownership, Profitability, Company Size, and Leverage on Tax Avoidance in Registered Consumption Goods Industry on IDX 2019-2021 - William William; Siti Dini; Wenny Anggeresia Ginting (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The aim of this research is to analyze and test the partial or simultaneous effects of institutional ownership, profitability, company size, and leverage on tax avoidance in the consumer goods industry listed on the IDX in 2019–2021. The study population consisted of 78 consumer goods companies listed on the Indonesia Stock Exchange (IDX), and the study sample consisted of 31 companies using a purposive sampling strategy. The methodology used in this research is a quantitative approach. Analysis using multiple linear regressions is the statistical technique used. The results of the partial t test for tax avoidance show that institutional ownership has an effect. While profitability, firm size, and leverage have no effect. Simultaneous F test for tax avoidance shows that institutional ownership, profitability, firm size, and leverage have no effect. The coefficient of determination of the study is 5.8%, while the remaining 94.2% can use other variables such as sales growth and audit committees which are not used in this study. The conclusion of this study for tax avoidance is tested partially, only institutional ownership has an effect.